Web-based panorama view of UiTM (Terengganu) Dungun Campus rental facilities / Nur Munirah Ismail - Ismail, Nur Munirah (2012)
The term Virtual Reality (VR) is used by many different people with different meanings, from the entertainment applications to complex scientific data visualization includes tourism, training, and manufacturing sectors. VR applications are used widely to create the illusions of realistic environment for the users. This project applied non-immersive VR that are 360 degree and 180 degree of Panorama View within an Online Reservation System that was developed to ease of the people outside the UiTM (Terengganu) and also for student and staff of UiTM (Terengganu) in making reservation for rental facilities provided. Panorama View and Online Reservation System for ‘Bahagian Pengurusan Fasiliti’ (BPF) UiTM (Terengganu) was developed by adapting ADDIE model as a methodology to achieve project objective. To develop the system, web development tools and techniques were used. For database, mySQL was used, PHP for server-side and scripting language, and Wampserver as a mini server. Evaluation of the Web-Based Panorama View was done by thirty candidates includes students, staffs and people outside UiTM (Terengganu). The result shown that the candidates interested and satisfied with the Web-Based Panorama View.